Approach to the concept of employability and its indicators: An Emple-AP case project - Bohórquez Arévalo, Luz Esperanza; Sierra Contreras, Alix Xiomara (Ingeniería Solidaria, 2020)
Introduction: This review article is the product of the research project Observatory for Labor Insertion and Strengthening of Employability in Countries of the Alliance of the Pacific (Emple-AP), developed at the Universidad Distrital Francisco José de Caldas in 2019. The aim of the project is to contribute to improving employability rates and the creation of a regional observatory. Problem: Employability is a complex social construct [1] [2], which varies depending on factors such as the actors involved and the focus emphasis. Objective: Build the concept of employability for the Emple-AP project, and, according to this, derive the indicators following the guidelines established for the creation of the employability observatory. Methodology: The construction of the concept is supported in the ontology design and validation of the results is performed by a panel of experts. Results: The results of the literature review regarding the concepts and employability rates are presented, followed by the design of the ontology and the employability construct that branches from it. Finally, employability indicators are designed and verified by the expert panel. Conclusion: Employability is defined according to the context in which it is immersed. Originality: Construct development under ontology design facilitates semantic heterogeneity problems, because it provides a conceptually shared language to represent information. Limitations: The construct is so complex and wide that it is necessary to perform several iterations under specialized methodologies until it is perfected.